Student Understanding of a Simple Heating Curve: Scientific Interpretations and Consistency of Responses - Paul G. Jasien (Seyit Ahmet Kıray, 2018)
This work seeks to elucidate undergraduate science students' basic knowledge of concepts related to the energy changes for a simple heating curve and their ability to integrate related concepts. The participants were drawn from first and second semester General Chemistry classes, as well as junior/senior level Physical Chemistry classes at a four-year public university in the United States. The research instrument for this study was developed and tested over an 18-month period from preliminary data from students at the same university. The data were analyzed for students' basic knowledge and the ability to make connections between related concepts. A definite lack of demonstrated skill in integrating multiple concepts was revealed at all student levels with respondents often giving inconsistent answers to related questions. It is suggested that these critical thinking skills can be cultivated in students through various active learning pedagogies based on explicit multi-concept problem solving exercises, rather than the usual simple ones that test concepts individually.